Guidelines for a Quechua Teaching Method for Receptive Bilinguals in Quechua - Meneses Tutaya, Norma (2020)
This article provides the most important results of an investigation carried out in 2017 in the Ayacucho region that had the objective of determining the theoretical and methodological guidelines necessary for a teaching method of Quechua for receptive bilinguals in Quechua from this region. This objective led us to carry out a state of the question on the studies of Quechua linguistics, linguistic application, applied linguistics and sociocultural studies on Andean communities that serve as the basis for such guidelines. Additionally, this review allowed us to show the need for new descriptive studies of the Quechua language and aspects of language planning of this language.